SMALL DENSE LOW-DENSITY LIPOPROTEIN CHOLESTEROL AND CENTRAL OBESITY ASSOCIATED WITH DIABETES MELLITUS AMONG INDONESIAN ADULTS - Yeni Rohmaeni; Hardinsyah Hardinsyah; Ikeu Tanziha (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: Small dense low-density lipoprotein (sdLDL-C) is an atherogenic lipoprotein. Increased sdLDL-C concentration was hypothesized to be associated with obesity and diabetes mellitus (DM).Objectives: The study aimed to determine the association between sdLDL-C, central obesity, and DM among Indonesian adults, controlled by personal and clinical parameters.Materials and Methods: This study used secondary data from Basic Health Research 2013 of the Ministry of Health, which applied a cross-sectional study design. For this purpose, 30,548 subjects aged 19-79 were analyzed. The sdLDL-C was performed by using Sampson Formula derived from conventional lipid panels. As investigated by Sampson, the formula referred to cLDL-C (calculated LDL-C) and ElbLDL-C (estimated large buoyant LDL-C).Results: There was a positive association between sdLDL-C and central obesity (OR: 3.94; 95% CI: 3.13-3.89), as well as sdLDL-C and DM status (OR: 1.98; 95% CI; 1.43-2.75) after adjusting the personal and clinical parameters.Conclusion: This study demonstrated that the increment of sdLDL-C level and central obesity affected DM status in Indonesian adults. It implies that the sdLDL-C was a potential biomarker to assess the risk of DM.Keywords: Central obesity, Diabetes mellitus, Hypertension, Indonesian adult, sdLDL-C